Development of BCR-ABL degradation inducers via the conjugation of an imatinib derivative and a cIAP1 ligand - Demizu, Yosuke; Shibata, Norihito; Hattori, Takayuki; Ohoka, Nobumichi; Motoi, Hiromi; Misawa, Takashi; Shoda, Takuji; Naito, Mikihiko; Kurihara, Masaaki (Bioorganic & medicinal chemistry letters, 2016)
[Display omitted] The manipulation of protein stability with small molecules has great potential as a technique for aiding the development of clinical therapies, including treatments for cancer. In this study, BCR-ABL protein degradation inducers called SNIPER(ABL) (Specific and Non-genetic inhibitors of apoptosis protein [IAP]-dependent Protein Erasers) were developed. The designed molecules contained two biologically active scaffolds: one was an imatinib derivative that binds to BCL-ABL and the other was a methyl bestatin that binds to cellular IAP 1 (cIAP1). The hybrid molecules, SNIPER(ABL), were expected to recruit BCR-ABL to cIAP1 for removal by proteasomes. In fact, SNIPER(ABL) induced the degradation of BCR-ABL protein and a subsequent reduction in cell growth. Thus, the degradation of BCR-ABL by SNIPER(ABL) is one potential strategy for treating BCR-ABL driven chronic myelogenous leukemia.